Stress Distribution Law of Full-Length Anchorage Bolt in Rectangular Roadway - Pang, Dongdong; He, Kai; Xu, Yatao; Chang, Jucai; Niu, Xingang; Li, Chuanming (Frontiers in Earth Science, 2022)
In order to study the evolution law of the axial force and the shear stress of the full-length anchorage bolt in rectangular roadway during roadway driving and working face mining, based on the stress analysis of the bolt, considering the elastic parameters and geometric size of the bolt, the effect of bearing plate on surrounding rock, roadway cross-section shape, roadway deformation degree, and roadway elastic parameters, the elastic mechanics and mathematical analysis methods were used to establish the mechanical model describing the interaction between the bolt and surrounding rock, and the mechanical formulas for calculating the axial force and the shear stress of bolt were derived. Taking the mining roadway of 1131(1) working face in Zhujidong coal mine of Huainan mining area as the engineering background, the axial force and the shear stress of the bolt in the middle of roof and side in rectangular roadway with the advance of driving face and working face were analyzed. The mechanical model and theoretical analysis results are verified by installing the force measuring bolts with the same mechanical properties as the field and observing the real axial force distribution of the bolts.